Use of thermographic imaging in clinical diagnosis of small animal: preliminary notes - Veronica Redaelli; Barbara Tanzi; Fabio Luzi; Damiano Stefanello; Daniela Proverbio; Lorenzo Crosta; Mauro Di Giancamillo (Istituto Superiore di Sanità, 2014)
INTRODUCTION. The authors, after a description of the physics of infrared thermographic technique (IRT), analyze the reading of images and the main applications in the veterinary field, compared to the existing literature on the subject and to their experimental researches. IRT lends itself to countless applications in biology, thanks to its characteristics of versatility, lack of invasiveness and high sensitivity. Probably the major limitation to its application in the animal lies in the ease of use and in its extreme sensitivity. MATERIALS AND METHODS. From September 2009 to October 2010, the experimental investigation with the thermo camera took into consideration 110 animals (92 dogs and 18 cats), without any selection criteria. All patients were brought to the Faculty of Veterinary Medicine in Milan University by the owner, to be examined by a specialist, or to undergo one of the following diagnostic procedures: X-rays, computed tomography, or ultrasound examinations; finally some patients were brought in for surgical procedures. With the consent of the owner, 1 to 10 thermographic images were recorded from each clinical case. Results. In this first experimental investigation, thermography has shown a high sensitivity (100%), but a low specificity (44%). This figure excludes the use of thermal imaging technology to replace other imaging techniques such as radiography, computed tomography and magnetic resonance imaging. Furthermore, it does not show any ability to recognize the etiology of the disease, but only the thermal alteration, and this is restricting its use. However, this experimental study has demonstrated that thermography can be used in veterinary medicine, and specifically in dogs and cats. It is hoped that in the field of targeted diseases this technique will become an important tool for diagnostic purposes by using working protocols validated and repeatable.